PENGARUH MENTAL HEALTH TERHADAP KINERJA MELALUI MOTIVASI KERJA PADA KARYAWAN BPJS KETENAGAKERJAAN MAKASSAR - Widayanti Yusuf; Ramlawati Ramlawati; Taupan Taupan (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the effect of mental health on employee performance, the effect of mental health on work motivation, the effect of work motivation on employee performance, and to examine the role of work motivation as an intervening variable in the relationship between mental health and employee performance at BPJS Ketenagakerjaan Makassar Branch. This research was conducted at the BPJS Ketenagakerjaan Makassar Branch Office, South Sulawesi, from January to February 2026. The population in this study consisted of all employees, totaling 91 individuals. The sampling technique used was the census method, where the entire population was taken as the research sample. The data used were primary data obtained through interviews and questionnaire distribution to respondents. Data analysis was carried out using path coefficient analysis based on Partial Least Squares (PLS) with the assistance of SmartPLS software. The results of the study show that: (1) mental health has a positive and significant effect on performance; (2) mental health has a positive and significant effect on work motivation; (3) work motivation has a positive and significant effect on employee performance at BPJS Ketenagakerjaan; and (4) work motivation significantly mediates the relationship between mental health and employee performance, indicating that improvements in employees’ mental health can enhance performance both directly and indirectly through increased work motivation.